Is It Whom You Know or What You Know? An Empirical Assessment of the Lobbying Process - Bertrand, Marianne; Bombardini, Matilde; Trebbi, Francesco (American Economic Review, 2014)
Do lobbyists provide issue-specific information to members of Congress? Or do they provide special interests access to politicians? We present evidence to assess the role of issue expertise versus connections in the US Federal lobbying process and illustrate how both are at work. In support of the connections view, we show that lobbyists follow politicians they were initially connected to when those politicians switch to new committee assignments. In support of the expertise view, we show that there is a group of experts that even politicians of opposite political affiliation listen to. However, we find a more consistent monetary premium for connections than expertise. (JEL D72, D82)